Toxicity of four kind plant extracts (Ageratum conyzoides L., Barringtonia asiatica (L.) Kurz., Melia azedarach L., Tephrosia vogelii Hook F.) against brown planthopper (Nilaparvata lugens STAL.) - Giannisa Febritami; N Usyati; Danar Dono (CROPSAVER, 2018)
One of the main pests that attack rice plants is the brown planthopper (BPH), Nilaparvata lugens. Awareness of the negative effects of synthetic insecticides that have been used to control BPH has encouraged the use of natural resources for crop protection. The plant is one of natural source that can be used in the crop protection. Some plant species that have been known to have insecticidal activities include Ageratum conyzoides (Asteraceae), Barringtonia asiatica (Lechytidaceae), Melia azedarach (Meliaceae) and Tephrosia vogelii (Fabaceae). In this study toxicity test of the plant extracts was carried out on BPH, and its phytotoxicity was observed in rice plants. In the toxicity test of the plant extracts against N. lugens and the phytotoxicity test on rice plants used 2 concentrations namely 0.1% and 0.5% from each plant extract, while the antioviposition test used a concentration of 0.5%. The results showed that the methanolic extract of T. vogelii with a concentration of 0.5% caused the highest mortality of brown plant hopper nymphs of 42.5% and at concentration of 0.5% the four plant extracts did not inhibit oviposition activity of N. lugens female and did not phytotoxic on rice plants.Keywords: Toxicity, anti oviposition, plant extract, brown planthopper